Historicism in the history of ideas. The youthful writings of the Argentine philosopher Rodolfo Agoglia (1920-1985) - Gatica, Noelia Liz (2022)
It analyses of the concept of «philosophical history of philosophy» proposed by Rodolfo Agoglia is investigated, under the assumption that his criticism introduces theoretical elements from historicism that are fruitful for studies of the History of Ideas. Through the methodological tools resulting from the transdisciplinary intersection of the History of Ideas and Practical Philosophy, the relevant characteristics are studied of its youth discursive production in the context of the professionalization of philosophy in Argentine universities and of the institutionalization of the History of Ideas in Latin America.